2015
DOI: 10.3346/jkms.2015.30.7.953
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude of 851 Nursing Personnel toward Depression in General Hospitals of Korea

Abstract: Our study aimed to examine the knowledge and attitude of nursing personnel toward depression in general hospitals of Korea. A total of 851 nursing personnel enrolled at four university-affiliated general hospitals completed self-report questionnaires. Chi-square tests were used to compare the knowledge and attitude of registered or assistant nurses toward depression. In addition, binary logistic regression analysis was used to adjust for the following confounders: age-group and workplace. Registered and assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…These results showed that comprehensive nursing care enhances the treatment for depression. Comprehensive nursing care, through psychological, exercise, and family interventions, can help the patients ameliorate the negative emotions, promote their interest, establish the correct life values, and open their mind, which are of great significance to the treatment of depression ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results showed that comprehensive nursing care enhances the treatment for depression. Comprehensive nursing care, through psychological, exercise, and family interventions, can help the patients ameliorate the negative emotions, promote their interest, establish the correct life values, and open their mind, which are of great significance to the treatment of depression ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted by Park et al (2015) and Youssef (2014) with nursing staff in Korean hospitals, indicate that the sample studied held the opinion that depression does not have a biological aetiology. In a study by Lauber et al (2003) conducted with a sample of the general population, over half of the sample attributed depression to family difficulties or issues with partners.…”
Section: "I Would Teach Her Relaxation Techniques To Help Her Calm Do...mentioning
confidence: 93%
“…In addition, screening for depression in general hospitals can improve the accuracy of detecting depressed patients ( 43 ) and the overall treatment of patients ( 44 ). Nurses are essential in screening, identification, and referral programs for depression in general hospitals’ physical disease management teams ( 45 , 46 ). A nurse-based model for early screening of depression in patients with physical illness in general hospitals has been proposed in Korea ( 46 ), and there are a few reports on such aspects in China.…”
Section: Introductionmentioning
confidence: 99%